Facets of classical university: Alexandr Sokurov’ art school in KBSU - Robert Kh. Kochesokov; KH. B. Mamsirov; E. M. Dymov (Высшее образование в России)
The article examines the role and forms of being of social and humanitarian science in contemporary classical university. By the example of cinema as a synthetic art it is shown how the problem of “two cultures” synthesis and the dialog of cultures can be solved.